PENGARUH LOKASI DAN ATMOSFER TOKO TERHADAP LOYALITAS PELANGGAN PADA ASIA TOSERBA TASIKMALAYA - Ilman Ansori (Jurnal Bisnis, Ekonomi, dan Sains, 2025)
The purpose of this study is to identify and analyze the influence of location and store atmosphere variables on customer loyalty at Asia Toserba Tasikmalaya. The research method used is a survey method. The sampling technique employed is accidental sampling, and the analytical tool used in this study is path analysis. Data were obtained directly through questionnaires distributed to 100 respondents, who were selected from customers of Asia Toserba Tasikmalaya. Based on the research results, it was found that location and store atmosphere have an influence on customer loyalty at Asia Toserba Tasikmalaya.